CRISPR/Cas9-based mutant library screening: the discovery of novel genes regulating immune responses in cotton and rice - Park, Sang Ryeol; Son, Seungmin (Frontiers in Plant Science, 2024)
The environmental conditions play a crucial role in determining crop yield, which is essential for ensuring food and nutritional security. However, rapid climate change is exacerbating global environmental stress, leading to severe biotic pressures on crops. Therefore, enhancing crop resilience to pathogens has become one of the most pressing challenges for humanity.Large-scale mutant library screening is the most efficient strategy for identifying numerous genes associated with specific traits. The revolutionary CRISPR/Cas9 system has ushered in a new era in the construction of mutant library. However, its application in crop plants has been relatively scarce compared to mammals, largely due to challenges in accessibility. Fortunately, several research groups have recently developed CRISPR/Cas9-based mutant libraries, successfully identifying a variety of genes involved in crop immunity. In this review, we present an overview and discussion of studies that have generated significant results through the use of CRISPR/Cas9 library screening to identify novel genes associated with resistance to biotic stresses within the field of plant research.